Evaluation of a 16-week Change Cycle for Ventilated Mouse Cages - Taylor, Jack L; Noel, Penny; Mickelsen, Michael (Journal of the American Association for Laboratory Animal Science, 2019)
The methods and conditions for housing research mice have been the subject of many discussions and publications in recent years. At our institution, we began to explore these matters with the goal of reducing stress in the animals and yet maintaining an environment that more closely resembled their habitat in the wild and yet was acceptable to researchers and the technicians that cared for the animals. Through a series of small inhouse studies, we derived a method that allowed the animals to stay in their established environment for longer than the standard 1- or 2-wk period. After several empirical studies, we concluded that the mice could stay in the same cage for 16 wk or perhaps even longer. To achieve this outcome, we perfected a method of removing 75% of the existing cage bedding and replacing it with clean bedding every 2 wk. To substantiate the validity of the method, we conducted a major study that evaluated the conditions of the cage, cage environment and the animals for a 16-wk period. In the study, we compared all of these factors in the 16-wk cages to a set of cages that were completely replaced on a 2-wk cycle. The mice in our study appeared to experience decreased stress, and observation also revealed that the 16-wk method was associated with increased pup survival in several colonies. The revised 16-wk method appears to create mouse cage conditions that are no different than the current standard (that is, every 1 or 2 wk) methods of cage changing.